"We Were Once"—A Quartets Game Aiming at Learning History Through Playing. Issue 3 (October 2020) - Marnin-Distelfeld, Shahar
This article deals with the card game "We Were Once" featuring the history of Kiryat Tivon. The game's components embody values expected to promote a sense of significance toward history among its young players. It consists of archival photos divided into 10 quartets: founders, mayors, beginnings, significant women, public buildings, first roads, events, children in schools, posters, and the reservoir. The game was designed to serve as a platform for creating pluralistic history, stressing the importance of visual literacy in learning processes. The game is analyzed in relation to its principles, such as historical continuity and gendered history.